TALABALARNING KREATIV KOMPETENTLIGINI RIVOJLANTIRIShDA DASTURIY TA’MINOTNING TARKIBIY QISMLARI - Seytmuratov, S.T. (SCIENCE and SOCIETY, 2025)
The article riches the components of the software for the development of creative competency of students, their role and significance in the current educational system.